Beyond Lifestyle for Sustainable Development: Learnings from the Dayalbagh Model - Dua, Pami; Allamraju, Ashita; Das, D Bhagwan; Dhir, Arsh; Sudhish, Prem Sewak (Economic and Political Weekly, 2025)
Addressing the intensifying environmental crisis requires a fundamental shift in societal functioning and the adoption of a lifestyle that prioritises sustainable development. Recognising this, India introduced the Lifestyle for Environment initiative at
Keywords: Dayalbagh Model; Environmental Crisis; Take-Make-Waste; Sustainable Development